Watermark Embedder and Detector for Medical Images: The Requirements and Design - Liew, Siau-Chuin; Jasni, Mohamad Zain (IEEE, 2010)
Watermarking had been proven to be able to protect medical images from unauthorized tampering and modification. Numerous watermarking schemes are available for different purposes depending on the security needs. Watermark embedding and detection process need to be performed in an efficient manner so that the operation of the health institution is not affected. This paper will focus on the development of a watermark embedding and detection application using existing tools from the design point of view to operate in a PACS (Picture Archiving and Communication Systems) environment.